A Study of the Preference of Some Feedback Methods in Teaching Second-Year Volleyball Students the Skill of the Spear-Shoot (Damu Journal of Sport Sciences, 2025)
In the introduction to the study, the researcher pointed out the importance of motor learning in leading learners to perform well, as it utilizes a variety of methods that directly influence learning. The problem was embodied in the question: Which feedback methods are most appropriate for the stage and skill to be taught? The study also aimed to identify the effectiveness of some feedback methods in teaching the skill of the spear-shoot in volleyball, and the preference of some methods. The human resource scope included second-year students from the College of Physical Education and Sports Sciences. The researcher used the experimental approach using groups (A, B, and C). The research community included (52) students, and the sample amounted to (45), with (15) students per group. To achieve the study objectives, the first group used a mixed feedback method, while the second group used a visual feedback method. The third group used a verbal feedback method. The researcher reached several conclusions, including:1-Feedback methods had a positive impact on the learning process of the coordinated serve skill.2- Mixed feedback is considered the most effective feedback method in the learning process of the coordinated serve skill.